2018
DOI: 10.2337/db17-1314
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive β-Cell Neogenesis in the Adult Mouse in Response to Glucocorticoid-Induced Insulin Resistance

Abstract: Both type 1 and type 2 diabetes are characterized by deficient insulin secretion and decreased b-cell mass. Thus, regenerative strategies to increase b-cell mass need to be developed. To characterize mechanisms of b-cell plasticity, we studied a model of severe insulin resistance in the adult mouse and defined how b-cells adapt. Chronic corticosterone (CORT) treatment was given to adult mice and led to rapid insulin resistance and adaptive increased insulin secretion. Adaptive and massive increase of b-cell ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…Any abnormality in the epigenetic regulatory mechanism will affect chromatin structure and gene expression, leading to the occurrence of a variety of diseases (Nilsson et al, 2018 ; Li S. et al, 2019 ; Perez and Lehner, 2019 ). Epigenetic changes are important regulatory mechanisms of islet β cell function and play irreplaceable roles in the normal physiological function of pancreatic β cells and insulin-secreting cells and apoptosis (Courty et al, 2019 ; Gong and Jiang, 2020 ; Makkar et al, 2020 ). There is no doubt that epigenetics research already becomes the focus of the study of pancreatic β cells in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Any abnormality in the epigenetic regulatory mechanism will affect chromatin structure and gene expression, leading to the occurrence of a variety of diseases (Nilsson et al, 2018 ; Li S. et al, 2019 ; Perez and Lehner, 2019 ). Epigenetic changes are important regulatory mechanisms of islet β cell function and play irreplaceable roles in the normal physiological function of pancreatic β cells and insulin-secreting cells and apoptosis (Courty et al, 2019 ; Gong and Jiang, 2020 ; Makkar et al, 2020 ). There is no doubt that epigenetics research already becomes the focus of the study of pancreatic β cells in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…This insulin sensitivity impairment after recovery period was probably due, at least in part, to the persistently increased WAT and lipid content in skeletal muscle (Geer et al 2014, Hamrick et al 2016. Moreover, it is worth noting that recent data from studies using the same adult mice model of CS report a marked positive effect on β-cell mass until 4 weeks after remission of hypercortisolism (Courty et al 2019), despite the toxic effects due to GC previously observed in vitro (Lambillotte et al 1997, Rafacho et al 2014. Compared with CORT, HFD treatment induced glucose intolerance and insulin resistance, which fits with the increased adiposity and lipid content in liver and skeletal muscle (Winzell et al 2007, Montgomery et al 2017.…”
Section: Figurementioning
confidence: 96%
“…In clinical studies, Van et al [8] found that after prednisolone treatment, there was an impaired glucose tolerance, reduced C peptide secretion stimulated by arginine, and islet cell dysfunction in healthy volunteers. However, some studies reported that islet β cell function and mass increased following glucocorticoid treatment, due to the body's compensatory effect [9,10]. Skeletal muscle is the main organ involved in insulin-mediated glucose uptake (> 80%).…”
Section: Introductionmentioning
confidence: 99%